RANCANG BANGUN ELEKTROKARDIOGRAPH BERBASISKAN PERSONAL COMPUTER (PC) - Salwin Anwar (Elektron : Jurnal Ilmiah, 2009)
Electrical signals of body are chemical’s respond of specific cell type. Electrocardiograph is used to record heart electrical activity which flow around the chest. This electricity flow is responded by sensor which acts as conductor. AD624AD is an instrument amplifier which is designed to transducer application with low level and pressure transducer. AD624AD has high precisions with low noise and input offside voltage less than 0,25 μV/0C. AD624AD not need pre-gain 1, 100, 200, 500 and 1000. An external resistor can be used to arrange the gain of AD624AD with level rating 1 up to 10.000 However, this equipment have input voltage to sensor 0,3 to 50 mV. The output voltage result from 1,6 to 5 volt using this amplifier.